2022
DOI: 10.1111/jce.15458
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk of energy drinks: Caffeine and taurine facilitate ventricular arrhythmias in a sensitive whole‐heart model

Abstract: Background Several case reports have suggested an increased risk of sudden cardiac death due to energy drinks. Therefore, the purpose of this study was to assess acute electrophysiologic effects of caffeine and taurine, two of the main ingredients of energy drinks, in an experimental whole‐heart model. Methods and Results Twenty‐five rabbit hearts were excised, retrogradely perfused, and assigned to two groups. Hearts were perfused with caffeine (2, 10, and 50 µM) or taurine (2, 10, and 50 µM) after generating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Possible adverse effects of caffeine and taurine on cardiac electrophysiology were investigated using twenty-five rabbits as an animal model [ 129 ]. The hearts of animals perfused with caffeine and taurine showed shortened repolarisation times and refractory periods on the ECG trace, followed by ventricular arrhythmias, confirming the potential arrhythmogenic effect of these substances.…”
Section: Discussionmentioning
confidence: 99%
“…Possible adverse effects of caffeine and taurine on cardiac electrophysiology were investigated using twenty-five rabbits as an animal model [ 129 ]. The hearts of animals perfused with caffeine and taurine showed shortened repolarisation times and refractory periods on the ECG trace, followed by ventricular arrhythmias, confirming the potential arrhythmogenic effect of these substances.…”
Section: Discussionmentioning
confidence: 99%
“…These result in a shortening of the repolarization period which explains the short QT interval, and short atrial and ventricular effective refractory periods. Ellermann et al 43 suggested that high-dose taurine may be responsible for the abbreviation of effective refractory periods. Moreover, there were some conflicting data in the literature which reported unchanged or increased QTc interval after ED consumption 7,8,23,44 .…”
Section: Discussionmentioning
confidence: 99%
“…Young people tend to take caffeine through energy drinks or soft drinks. The incidence of atrial fibrillation in young people is very low; however, some case reports illustrate arrhythmic episodes as a consequence of the assumption of high doses of energy drinks [5,[94][95][96][97][98][99].…”
Section: Limitationsmentioning
confidence: 99%